Content Analysis oflndian State Tourism Websites - Sharma , Nitasha (Gyan Management Journal, 2017)
Tourism Industry is one of the most profitable industries which is contributing a substantial amount to foreign exchange, employment and GDP of India. The credit for increased GDP, employment and foreign exchange earnings by Tourism sector in Indian Economy goes to increased rate of foreign tourist arrivals. In the past, tourists had to depend on the brochures drafted by Indian Tourism Development Corporation (/TDC) and other State Tourism Corporations for detailed information related to their trip. However, with advancement in the information technology, traditional marketing approach was slowly replaced by internet based tools. Various tourism promotion agencies have developed their websites to attract more and more national and international tourists. Current study is an attempt to examine the significant difference in information displayed by tourism websites of different zones of India. Data was collected through secondary sources for total 73 variables. Further these 73 variables have been divided into 4 categories Informational, Communicational, Transactional and Website Management. Multivariate Analysis (MANOVA) was applied to pursue the current objective. Results depicted that overall West Indian tourism websites are the best among all tourism websites as far as Informational, Communicational, Transactional and Website Management categories are concerned followed by North Indian tourism websites and South Indian tourism websites.